2014
DOI: 10.1517/17425255.2014.947263
|View full text |Cite
|
Sign up to set email alerts
|

Hydralazine–valproate: a repositioned drug combination for the epigenetic therapy of cancer

Abstract: Drug repositioning is a strategy for prompt and cost-efficient drug discovery. There is evidence that combining DNMTi with HDACi would be more efficacious than administering each agent on its own. Hydralazine-valproate is safe when used alone or in combination with chemotherapy or chemoradiation. The fact that both drugs are orally administered is another advantage over current epigenetic drugs. This combination is promising but larger studies are needed. Among these, the randomized Phase III trials in advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…These novel drugs show higher potency and specificity targeting other enzymes, including bromodomain and extra terminal protein (BET), lysine-specific demethylase 1A (LSD1/KDM1A), mutant isocitrate dehydrogenase (IDH), histone methyltransferase (HMT) and protein arginine methyltransferase (PRMT). A recent but promising trend in the cancer treatment landscape is combination therapies of epigenetic drugs with other compounds ( Dueñas-Gonzalez et al, 2014 ; Ahuja et al, 2016 ; Raynal et al, 2017 ). Epigenetic inhibitors could be the lead to treat multiple disease types apart from cancer.…”
Section: Interventions and Future Aspectsmentioning
confidence: 99%
“…These novel drugs show higher potency and specificity targeting other enzymes, including bromodomain and extra terminal protein (BET), lysine-specific demethylase 1A (LSD1/KDM1A), mutant isocitrate dehydrogenase (IDH), histone methyltransferase (HMT) and protein arginine methyltransferase (PRMT). A recent but promising trend in the cancer treatment landscape is combination therapies of epigenetic drugs with other compounds ( Dueñas-Gonzalez et al, 2014 ; Ahuja et al, 2016 ; Raynal et al, 2017 ). Epigenetic inhibitors could be the lead to treat multiple disease types apart from cancer.…”
Section: Interventions and Future Aspectsmentioning
confidence: 99%
“…Studies conducted with ESCC and esophageal adenocarcinoma (EAC) cells, in vitro as well as in human esophageal carcinomas, demonstrated decreased cell migration. Furthermore, the combination of the DNMT inhibitor hydralazine-valproate and an HDAC inhibitor were applied for the treatment of CTCL [103]. The phase I trial confirmed safe drug administration, although additional studies are required to demonstrate efficacy.…”
Section: Cancer and Epigeneticsmentioning
confidence: 96%
“…The mechanism of action of hydrazaline is still a controversial issue as some groups claimed that it binds to the catalytic site of DNMT, while others reported that it reduces DNMT1 and DNMT3a expression via the extracellular signal–regulated kinase (ERK) pathway inhibition [132,133]. This drug is in different phases of clinical trials as an anticancer drug, and registered in Mexico in combination with an HDAC inhibitor, i.e., magnesium valproate, for MDS treatment [134,135]. …”
Section: Inhibition Of Dna Methylation: Other Approachesmentioning
confidence: 99%